Molecular and morphological evidence for a unified, inclusive Sinotaia quadrata (Caenogastropoda: Viviparidae: Bellamyinae). (9th July 2021) - Ye, Bin; Hirano, Takahiro; Saito, Takumi; Dong, Zhengzhong; Do, Van Tu; Chiba, Satoshi
ABSTRACT: The taxonomy of species in the caenogastropod genus Sinotaia (Viviparidae: Bellamyinae) has been a complex and controversial issue since the 19th century. Sinotaia quadrata, the type species of Sinotaia, comprises many named forms and transitions between them, and the taxonomic validity of some species similar to S. quadrata also requires clarification. To clarify relationships in this common and significant member of the freshwater benthos, we reconstructed a phylogeny for species related to S. quadrata based on the 16S rRNA and cytochrome c oxidase subunit I genes to test which classifications are robust using modern data and interpretation. We also compared the shell outline morphology of type material of most species in the genus Sinotaia from the original literature. The combination of phylogenetic and shape variance data suggests that seven currently recognized species of Sinotaia should be synonymized with S. quadrata . We used microsatellite markers and landmark-based geometric morphometric analysis to examine the genetic differentiation and shell shape variation of S. quadrata populations in both China and Japan. Genetic and shape variations were not congruent, suggesting that minor variations in shell shape do not indicate distinct Sinotaia species. Shell shape variation shows no clear separations and shows environmental plasticity. Using data on molecular phylogenetics, genetic diversity and shell morphology, we provide a more inclusive species concept for S. quadrata . This provides a basis to formally revise this taxon and the seven closely related nominal species that are widely distributed in China and East Asia.